Pengaruh Penerapan Konsep Smart Village terhadap Pembangunan Desa Berbasis Digital di Pekon Yogyakarta Selatan - martin, Afrizal; w, Widianto; m, Mardiyanto; joni, Joni (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The Smart Village concept emphasizes the development of rural communities that are independent and competitive through the utilization of Information and Communication Technology (ICT) to improve the quality of life. This concept encompasses several dimensions, including smart people, smart mobility, smart government, smart economy, smart living, and smart environmental management. This study aims to examine the implementation of the Smart Village concept and analyze its impact on village development in Pekon Yogyakarta Selatan, Gadingrejo District, Pringsewu Regency. The research employed a descriptive quantitative method. Data were collected through documentation, interviews, and the distribution of questionnaires to the local community. The findings indicate that the implementation of the Smart Village concept has a significant positive impact on the development of Pekon Yogyakarta Selatan, particularly in aspects of government services, improvement of human resources quality, and strengthening of the local economy. These results demonstrate that the Smart Village initiative in Pekon Yogyakarta Selatan has been effectively implemented and contributes to sustainable village development.